MERETAS MASALAH PERPANGANAN DI KABUPATEN ALOR: DULU, KINI, DAN MASA MENDATANG - Robert Siburian (Jurnal Masyarakat dan Budaya, 2011)
Alor is a district in East Nusa Tenggara Province that often suffers from food shortage. Food insecurity experienced by farmer community is mainly related to two main factors, namely: geography condition and accessibility of people to food resources. Those situations have created low agricultural production, which have their close nexus with farmersâ€™ income. As a consequent, they seek of getting financial assistance, whether from government or private sectors. Some factors that are contributing to farmers low income including land infertility, farmers possession of a small plot of land, the scarcity of productivity means such as: fertilizers, the weather condition (dry season) and natural disasters. Most importantly, the limited skills of farmers to make use by all resourcesavailable factors has also impacted to food insecurity. To overcome the current condition, any effort to establish food security mechanism through alleviation of poverty programs is recommended, for example, the revitalization of Alor local food. In the long run, any development of agricultural program in Alor Island must be carried out through intensification and extensification programs as well as accelerating aquacultural program and other alternative solutions. Strengthening the local â€œadatâ€ organizations could also help farmers inparticular to cope with the food insecurity, and to solve related major issues that link closely with people basic needs. The data used to write this paper are based on research conducted on September and October 2009.Keywords: Food Security, Revitalization, and Local Food